Co-researching with Students: Exploring the Value of Class Discussions - Karen Hume (Networks: An Online Journal for Teacher Research, 1998)
Knowledge building is a term that's meant to suggest a particular stance in my classroom - a focus by all participants on knowledge as an object that is both constructed and continually improved through the multiple perspectives and competing viewpoints that we bring to a question. As various perspectives are raised, students marshal evidence to support their views and to contribute to the building of our collective understanding. Knowledge building, therefore, like almost all classroom activity, relies on oral and written discourse.